2015
DOI: 10.1007/s00284-015-0888-5
|View full text |Cite
|
Sign up to set email alerts
|

Plant Pathogenic Microbial Communication Affected by Elevated Temperature in Pectobacterium carotovorum subsp. carotovorum

Abstract: Gram-negative plant pathogenic bacteria regulate specific gene expression in a population density-dependent manner by sensing level of Acyl-Homoserine Lactone (HSL) molecules which they produce and liberate to the environment, called Quorum Sensing (QS). The production of virulence factors (extracellular enzyme viz. cellulase, pectinase, etc.) in Pectobacterium carotovorum subsp. carotovorum (Pcc) is under strong regulation of QS. The QS signal molecule, N-(3-oxohexanoyl)-L-Homoserine Lactone (OHHL) was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…For example, Vibrio growth dynamics and competitiveness in coral mucus and tissues has been demonstrated to be linked to QS signaling molecules such as N -acylhomoserine lactones (AHLs) (Henke and Bassler, 2004; Tait et al, 2010; Certner and Vollmer, 2015). These Vibrio- derived QS molecules are also influenced by environmental factors such as temperature (Tait et al, 2010; Saha et al, 2015) with QS mechanisms breaking down under stress conditions that disrupt the associated microbiome. Certner and Vollmer (2015) demonstrated that resident microorganisms can opportunistically cause white band disease in Acropora cervicornis and that this seems to be regulated by a quorum-sensing signaling molecule.…”
Section: Bmc Mechanismsmentioning
confidence: 99%
“…For example, Vibrio growth dynamics and competitiveness in coral mucus and tissues has been demonstrated to be linked to QS signaling molecules such as N -acylhomoserine lactones (AHLs) (Henke and Bassler, 2004; Tait et al, 2010; Certner and Vollmer, 2015). These Vibrio- derived QS molecules are also influenced by environmental factors such as temperature (Tait et al, 2010; Saha et al, 2015) with QS mechanisms breaking down under stress conditions that disrupt the associated microbiome. Certner and Vollmer (2015) demonstrated that resident microorganisms can opportunistically cause white band disease in Acropora cervicornis and that this seems to be regulated by a quorum-sensing signaling molecule.…”
Section: Bmc Mechanismsmentioning
confidence: 99%
“…Thus, the upregulation of these loci under high Finally, some studies have reported a negative regulation of virulence under higher temperatures. A recent study (Saha et al, 2015) analyzed the effect of an array of temperatures (18 to 37 °C) on the phytopathogenic bacterium Pectobacterium carotovorum, responsible for bacterial soft rot in a wide range of plant species. The authors identified an optimal temperature (33°C) for the production of the quorum-sensing signal molecule, acyl homoserine lactone, which regulates bacterial population and virulence gene expression.…”
Section: Temperature Stress and Virulence Genes: The Pathogen Point Of Viewmentioning
confidence: 99%
“…The Peh activity of Pcc, Pbr, and Ppo at 37°C was half of that at 28°C, but Pel activity showed no change except for Ppo. It is well known that PCWDEs are controlled by quorum sensing (QS), and the QS signal molecule, N -(3-oxohexanoyl)-lhomoserine lactone, is not detectable at 37°C ( Hasegawa et al, 2005 ; Põllumaa et al, 2012 ; Saha et al, 2015 ). Golanowska et al (2017) showed that Cel activity of Dickeya species was mainly regulated by temperature, but there was a larger effect of species on pectinase and Prt activities.…”
Section: Resultsmentioning
confidence: 99%